Solve for k k/-4=13

Math
k-4=13
Multiply both sides of the equation by -4.
-4⋅k-4=-4⋅13
Simplify both sides of the equation.
Tap for more steps…
Simplify -4⋅k-4.
Tap for more steps…
Cancel the common factor of 4.
Tap for more steps…
Factor 4 out of -4.
4(-1)⋅k-4=-4⋅13
Factor 4 out of -4.
4⋅-1⋅k4⋅-1=-4⋅13
Cancel the common factor.
4⋅-1⋅k4⋅-1=-4⋅13
Rewrite the expression.
-1⋅k-1=-4⋅13
-1⋅k-1=-4⋅13
Simplify the expression.
Tap for more steps…
Move the negative one from the denominator of k-1.
-1⋅(-1⋅k)=-4⋅13
Rewrite -1⋅k as -k.
-1⋅(-k)=-4⋅13
-1⋅(-k)=-4⋅13
Multiply -1(-k).
Tap for more steps…
Multiply -1 by -1.
1k=-4⋅13
Multiply k by 1.
k=-4⋅13
k=-4⋅13
k=-4⋅13
Multiply -4 by 13.
k=-52
k=-52
Solve for k k/-4=13

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top